Structural and optical temperature-dependent properties of PbS thin films deposited by radio frequency sputtering - da Silva Filho, José Maria Clemente; Marques, Francisco Chagas (Materials science in semiconductor processing, 2019)
Lead sulfide (PbS) thin films deposited by radio frequency (RF) sputtering, in the 50–300 °C temperature range, were the subject of our investigation. We characterized the influence of deposition temperature on their structural, morphological, and optical properties by x-ray diffraction (XRD), atomic force microscopy (AFM), and UV–visible and Raman spectroscopy. XRD revealed that a transition from an amorphous to a crystalline structure occurs in the 200–250 °C temperature range. One was also able to observe an increase in grain size (determined by AFM), as the temperature increased. We also found that a broad range of band gaps (from 0.72 eV to 2.12 eV) might also be obtained by varying the deposition temperature.